Are native cyprinids or introduced salmonids stronger regulators of benthic invertebrates in South African headwater streams?. (13th May 2016) - Shelton, Jeremy M.; Samways, Michael J.; Day, Jenny A.; Woodford, Darragh J.
Abstract: The introduction of nonnative salmonids in the Southern Hemisphere generally leads to a reduction in invertebrate abundance and changes in assemblage composition. In the Cape Floristic Region of South Africa, introduced rainbow trout Oncorhynchus mykiss is the dominant predator in many headwater streams, where they have replaced small‐bodied native fishes such as Breede River redfin Pseudobarbus burchelli . To examine the consequences of this species replacement on food web structure, we used a month‐long field experiment to compare the top‐down effects of Breede River redfin and rainbow trout on benthic invertebrate assemblages (abundance and composition) and basal resources (periphyton and particulate organic matter) in 1 × 1.5 m of plastic cages. Benthic invertebrate abundance was more strongly depleted in the cages with redfin than in the cages with trout, and redfin and trout had distinct effects on invertebrate assemblage composition. On the other hand, neither redfin nor trout had a significant influence over standing stocks of periphyton or organic matter, implying that their differential effects on benthic invertebrates did not cascade down to the base of the stream food web in our experiment. Gut content analysis showed that aquatic invertebrates contributed more to the diet of redfin, while terrestrial invertebrates contributed more to the diet of trout, which may be responsible for the relatively weak effect of trout on aquatic invertebrates. This pattern contrasts with nonnative salmonid impacts elsewhere in the Southern Hemisphere. That trout can strongly alter the structure of benthic invertebrate assemblages, in addition to severely depleting native fish abundance, in Cape Floristic Region headwater streams should be weighed into management decisions, and our findings highlight the need for a detailed understanding of species‐specific top‐down effects where native predators are replaced by invasive predators.